Information sources among students in UiTM Puncak Perdana campus in completing their assignments / Noor Suriati Abu Hasan - Abu Hasan, Noor Suriati (Faculty of Information Management, 2008)
This research was conducted to investigate the information sources that need by the students from Universiti Teknologi MARA Puncak Perdana Campus, Shah Alam, Selangor. The purpose of this research was to investigate the types of information sources used by the students in finding the information for their assignments. Furthermore, it was also concerned on their preferred format of materials used in searching for information, the importance of the selected information sources and also the reasons for using certain information sources when the students needed for completing their assignments excellently and successfully. A questionnaire was distributed to 100 randomly selected students and greatly all the 100 sets of questionnaire were returned to the researcher. The result of the research was found that electronic sources were the preferred information sources format among the students in this university. Thus, the findings recommend a library should enhance their information sources in collection in order to ensure the students have complete information for their assignments to done successfully and appropriately.